2016
DOI: 10.1021/acs.jpcc.6b07401
|View full text |Cite
|
Sign up to set email alerts
|

Structures of Nanoalloy Clusters AunAln(n= 1–10) and the Growth Patterns to the Bulk Phase

Abstract: Gold nanoclusters have attracted intense interests due to their unique applications as catalysts. The properties of the gold clusters can often be extended through alloying with other metals, by virtue of adding new degrees of freedom and increasing the versatility of bonding. Here, we reported a new series of bimetallic clusters Au n Al n (n = 1−10) determined from the density functional calculations. Particle swarm global minimum searches, coupled with density functional optimization, were used to identify l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 64 publications
0
4
0
Order By: Relevance
“…A negative value of mixing enthalpy indicates a favorable mixing tendency. When we used the CALYPSO method to predict structures, 34,35 at least 1000 isomers were probed on the same molecular formula to achieve a lower energy structure, and the 30 lowest energy isomers were further optimized to predict the ground state structure. …”
Section: Calculation Methodsmentioning
confidence: 99%
“…A negative value of mixing enthalpy indicates a favorable mixing tendency. When we used the CALYPSO method to predict structures, 34,35 at least 1000 isomers were probed on the same molecular formula to achieve a lower energy structure, and the 30 lowest energy isomers were further optimized to predict the ground state structure. …”
Section: Calculation Methodsmentioning
confidence: 99%
“…Among these dopants, Al has received considerable attention due to its low cost and high abundance. Progressive research works have unearthed the rich structures of alloyed Au x Al y , varying from Al-rich AuAl n (n = 1-15) to Aurich Au 5 Al, by PES, high-resolution photoelectron imaging and first-principles calculations [34][35][36][37][38][39][40]. Furthermore, Alcontaining alloy nanostructures have also been reported to have potential in many fields, such as hydrogen storage [41,42], and carbon monoxide (CO) and nitrogen monoxide adsorption [43].…”
Section: Introductionmentioning
confidence: 99%
“…When clusters or atoms contact the substrate, physical or chemical adsorptions occur due to the interaction schemes and kinetic energies of the 0D objects [49]. Along with tailored optic and electronic properties [50], the guest clusters are endowed with tunable magnetism and chemical reactivity [51,52], which allows them to act as essential building bricks for functional nanomaterials [53]. A previous doping strategy showed that replacing both the Mo and S atoms with FeX 6 (X = S, C, N, O, F) clusters allowed for intrinsic ferromagnetism to be brought into the cluster-doped stable slabs [54].…”
Section: Introductionmentioning
confidence: 99%